Effect of Al replacing Si on mechanical properties of high carbon Q–P–T martensitic steels. Issue 1 (3rd April 2019) - Zhang, Jiazhi; Qin, Shengwei; Liu, Yu; Zuo, Xunwei; Chen, Nailu; Rong, Yonghua
ABSTRACT: Fe–0.67C–1.55Mn–1.99Al–0.60Cr–0.038Nb (Fe–2Al) and Fe–0.63C–1.52Mn–1.49Si–0.62Cr–0.036Nb (wt.%) (Fe–1.5Si) were designed and both subjected to novel quenching–partitioning–tempering (Q–P–T) process, and the effect of 2 wt.% Al replacing 1.5 wt.% Si on mechanical properties was studied. The Fe–2Al Q–P–T martensitic steel exhibited a tensile strength of 1640 MPa and elongation of 21.1% accompanied with product of strength and elongation (PSE) of 43.65 GPa %, which is superior to the third generation advanced high strength of 30 GPa %. While the tensile strength of Fe–1.5Si Q–P–T martensitic steel is 1.950 GPa, and the total elongation only is 12.4%, whose PSE is less than 30 GPa %. High ductility of Fe–2Al Q–P–T martensitic steel origins from that the dislocation absorption by retained austenite effect and high mechanical stability of retained austenite due to the addition of Al, which avoids the formation of more brittle strain –induced twin-type martensite from retained austenite transformation. The lower strength of Fe–2Al Q–P–T steel than Fe–1.5Si Q–P–T steel is attributed to lower elastic modulus of former steel after Q–P–T process.